Cystoid Macular Edema (CME) - Arfini Mertia M; Saiful Basri (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Cystoid Macular Edema (CME) is one of the most common causes of vision loss in postoperative cataract patients. CME occurs due to fluid accumulation in the subretinal space due to increased permeability of perifoveal capillaries and intra-ocular vascular instability which is a consequence of disruption or damage to the blood barrier layer of the retina. This condition occurs in 20% after cataract surgery, 1% of whom have clinical symptoms in the form of a significant decrease in vision. Provision of medicamentose therapy after surgery can optimize sharp vision and treat CME. The patient who entered from the poly RSUDZA was an 82-year-old man with complaints of blurred left eye and winding vision since the patient sneezed 1 week after cataract surgery. Patients are given artificial tears eye drops and topical NSAIDs as well as education for drug adherence. The response to therapy is quite good where there is improvement in vision and on OCT examination there is a reduction in macular thickness.